Short communication: dietary oregano essential oil supplementation promotes tibial bone mass and size but not density or strength in growing lambs - Wu, Xuejing; Zhang, Guiguo; Jonker, Arjan; Sun, Xuezhao (Frontiers in Animal Science, 2025)
Bone development is essential for the growth, welfare, and long-term productivity of growing lambs. This study aimed to assess the effects of dietary oregano essential oil (OEO) supplementation on tibial morphology, mineralization, and mechanical properties in lambs. Twelve healthy, 3-month-old male lambs (Small-tailed Han × Black-boned cross, average liveweight 30.8 ± 0.4 kg) were randomly assigned to either a control group or a group receiving OEO at 0.5 g/kg of feed for 76 days. Tibiae were collected post-slaughter for morphometric and mechanical analysis. Tibiae were assessed for weight, length, bone mineral content (BMC), bone mineral density (BMD), bone area, bone volume, and breaking strength. Data were analyzed using independent sample t-tests, with significance set at P < 0.05. OEO supplementation significantly increased tibia weight (14.4%), BMC (19.7%), bone area (12.2%), and bone volume (19.6%) (P < 0.05). Tibia length, BMD, and breaking strength showed numerical increases but were not statistically significant. These findings suggest that bone mass and size may be more responsive to short-term dietary intervention than density or mechanical strength. This study provides original evidence that short-term OEO supplementation in lambs primarily promotes bone mass accretion and structural expansion rather than immediate improvements in density or mechanical strength. These findings expand the understanding of plant-derived feed additives in small ruminant bone health and suggest a potential strategy to enhance skeletal growth, warranting further research on long-term functional outcomes.